Financial Incentives and Fertility - Cohen, Alma; Dehejia, Rajeev; Romanov, Dmitri (The Review of Economics and Statistics, 2013)
Using panel data on over 300,000 Israeli women from 1999 to 2005, we exploit variation in Israel's child subsidy to identify the impact of changes in the price of a marginal child on fertility. We find a positive, statistically significant, and economically meaningful price effect on overall fertility and, consistent with Becker (1960) and Becker and Tomes (1976), a small effect of income on fertility, which is negative at low and positive at high income levels. We also find a price effect on fertility among older women, suggesting that part of the overall effect is due to a reduction in total fertility.